Navigating urban life in Lisbon: a study of migrants’ mobilities and use of space - Buhr, Franz (2018)
Besides a more general concern over transport infrastructure, its quality and availability, mobility is also a pre-condition for city dwellers to access urban resources, facilities, employment, local services and leisure. Moreover, mobility allows urban inhabitants to uncover a city’s potentialities and to fully participate in urban life. Migrants, nevertheless, face the issue of learning to do mobility in a new environment together with the urgency for settlement, finding work, making personal connections and attending to the mundane needs of everyday life that require one to move about. This article looks at migrants’ urban mobilities in Lisbon, Portugal, from two perspectives. First, we look at migrants’ urban knowledge and skills and at how they employ their abilities to use Lisbon’s urban resources. Second, we address some of the ways placespecific urban resources of a religious nature sustain and are sustained by various (im)mobility practices. More specifically, we look to a suburban mosque run by Guinean migrants and to a Sikh Gurdwara. This mobile/place-based contrast points to the variegated (and often overlooked) forms of mobility (or lack of) that are put to practice by migrants and to how they shape the everyday of migration journeys and their capacities to enjoy city-living.